Dante: A New Pauline Apostle? - Daigle-Williamson, Marsha (Christian scholar's review, 2010)
In this essay, Marsha Daigle-Williamson notes that in the Divine Comedy, Dante sets up parallels between his pilgrim and St. Paul, especially in the third part of his poem, to suggest that he is a new Pauline apostle. However, because of an overlapping identification between Dante the poet and Dante the pilgrim, by extension the poet is presenting himself indirectly as an apostle in the Pauline tradition. Daigle-Williamson looks at how Dante constructs this claim and then examines whether it is valid or not.